TYPOLOGY OF BUILDINGS FOR TEMPORARY ACCOMMODATION OF PERSONS SUFFERING DUE TO LIQUIDATION OF EARTHQUAKE CONSEQUENCES IN CHINA - Bi Xin (Наука и техника)
The  location of China in a zone of high danger for occurrence of various natural disasters requires a constant readiness for fast execution of construction works pertaining to creation of temporary camps for accommodating the victims. Creation of such settlements where people can live for 5 years, is ensured in different directions, including architecture as well. For this purpose it is necessary to use such types of buildings which can be built within a short period of time and which can provide comfort for residing, conditions for elimination of stresses and realization of psychological rehabilitation. An analysis of the accumulated Chinese experience on temporary camp creation for liquidation of natural disaster consequences allows to determine the most optimum types of buildings and develop recommendations for their improvement